Preparation, motion study and application of autonomous micro and nano devices - Maric, Tijana (Nanyang Technological University, 2020)
Micro- and nanomachines are a new generation of nanotechnology, allowing nano- and micro-objects to propel themselves, perform autonomous motion and other on demand actions, such as drug delivery or environmental remediation. Micromotors are microscale devices which are made to perform various types of movements. They are an upcoming topic of today's research due to their interesting size and multiple potential uses. In the last decade, scientists have become increasingly interested in these devices. Autonomous self-powered miniaturized machines are the next step for nanotechnology. They consist of different types of micro- and nanoscale compounds, and can be propelled using various sources of energy inputs. The versatility of new nanomaterials coupled with emerging catalysts, has enabled fabrication of different micro- and nanomotors suitable for detection of water pollutants but also for cargo delivery in biomedicine. In this thesis, black phosphorus, 2D germanene and TiO2 nanoparticles were studied as promising materials for micro- and nanomotors preparation and they exhibited very efficient motion properties in aqueous media. Natural nanoclays and pollen micromotors were shown as excellent and cheap adsorbents which were used to reduce concentration of various pollutants in water. Henceforth, this research is focused on the use of natural micro and nanoparticles for preparation of micromotors that have suitable properties of adsorbents. Furthermore, our study was based on the stability and durability of micromotors over prolonged periods of time with a focus on the influence of ageing in “storage” conditions- the difference in performance of ‘freshly prepared’ and ‘old’ micromotors could have a significant impact on the reliability and reproducibility of the micromotors. From our findings, it was discovered that the performance and morphologies of ‘new’ and ‘old’ differ greatly over the period of study. As such, it would be of importance to prepare new batches of micromotors for enhanced efficiency and reproducibility of experimental analysis.